ASSESSMENT OF INTERNAL LABOR MIGRATION ON THE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Nina A. Eldyaeva; Ekaterina S. Kovanova (Статистика и экономика)
The author, based on a sample survey of internal labor migration assesses its impact on the socio-economic development of the Republic of Kalmykia. Despite the development of administrative sources of data on migration, much of the data can only be obtained through sample surveys. The survey found the volume and scope of internal labor migration, provided an assessment of the structural characteristics of the population, identified the causes of migration and to assess the extent of the return of internal labor migration; The effect of migration on living standards in the region and on the balance of the local labor market.